Formulasi Sistem Vesikel Elastik Surfaktan Nonionik Ekstrak Etanol Rimpang Etlingera alba dalam Sediaan Gel: Formulation of Nonionic Surfactant Elastic Vesicle System of Etlingera alba Rhizome Ethanolic Extract in Gel Preparation - Astrid Indalifiany; Suryani; Wahyuni; Sahidin; Wa Ode Erna Fitriani (Fakultas Farmasi Universitas Halu Oleo, 2023)
Etlingera alba is a plant in Southeast Sulawesi that has antioxidant activity. Natural ingredients such as herbal medicine require a delivery system that facilitates them to reach the site of drug action, especially for transdermal delivery. The elastic vesicle system is a transdermal delivery system that can increase the penetration of active substances at the skin through the act of phospholipids on the skin's lipid bilayer and the deformability of the vesicles. This study aims to formulate and evaluate Etlingera alba rhizome ethanolic extract's elastic vesicle gel to obtain the optimal concentration of Tween 60 as a vesicle former and carbopol as a gel base. Preparation of elastic vesicles of Etlingera alba ethanolic extract using the heat method through variations Tween 60's concentration, namely 5%(F1); 10%(F2); 15%(F3); and 20%(F4). Meanwhile, elastic vesicle gel formulation of the ethanol extract of Etlingera alba rhizome used various concentrations of 0.5% carbopol gel base (FGel 1); 1% (FGel 2); 1.5% (FGel 3); and 2% (FGel 4). The results obtained were the optimum concentration of Tween 60 as a constituent of elastic vesicles of 15% (F4) with spherical morphology using an optical microscope, vesicle size of 10.45 nm, and polydispersity index of 0.280 using a Particle Size Analyzer. In addition, the optimal concentration of carbopol as a base for elastic vesicle gel is a concentration of 0.5% (GGel 1) with white color, distinctive aroma, and thick texture, and has a pH of 6, a viscosity of 2,366 cPs, spread of 6.8 cm, and physically stable through cycling test.